Enzymology of acyl chain macrocyclization in natural product biosynthesis - Kohli, Rahul M.; Walsh, Christopher T. (Chemical communications (Cambridge, England), 2003)
Polyketides and nonribosomal peptides constitute a large and diverse set of natural products with biological activity in microbial survival and pathogenesis, as well as broad pharmacological utility as antineoplastics, antibiotics or immunosupressants. These molecules are biosynthesized by the ordered condensation of monomer building blocks, acyl-CoAs or amino acids, leading to construction of linear acyl chains. Many of these natural products are constrained to their bioactive conformations by macrocyclization whereby, in one of the terminal steps of biosynthesis, parts of the molecule distant in the constructed linear acyl chain are covalently linked to one another. Typically, macrocyclization is catalyzed by a thioesterase domain at the C-terminal end of the biosynthetic assembly line, although alternative strategies are known. The enzymology of these macrocyclization catalysts, their structure, mechanism, and catalytic versatility, is the subject of this review. The diversity of macrocyclic structures accessed by enzyme catalyzed cyclization of linear acyl chains as well as their inherent substrate tolerance suggests their potential utility in reprogramming natural product biosynthesis pathways or accessing novel macrocyclic structures.